2011
DOI: 10.1007/s13197-011-0607-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packaging materials and storage environment on postharvest quality of papaya fruit

Abstract: This experiment was conducted to assess the effects of packaging materials and storage environments on shelf life of papaya fruit (Carica papaya L.). A factorial combination of five packaging materials and two storage environments using randomized complete block design with three replications were used. The papaya fruits were evaluated for weight loss, percentage marketability, firmness, total soluble solids, pH, titratable acidity, ascorbic acid, reducing sugar and total sugar content. The packaged and cooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 44 publications
7
40
0
1
Order By: Relevance
“…These results corroborate the findings of Azene et al (2011) and Gómez et al (2002), in which the amount of SS had no significant changes during ripening of papaya fruit, with values of nearly 12%.…”
Section: Sssupporting
confidence: 90%
See 1 more Smart Citation
“…These results corroborate the findings of Azene et al (2011) and Gómez et al (2002), in which the amount of SS had no significant changes during ripening of papaya fruit, with values of nearly 12%.…”
Section: Sssupporting
confidence: 90%
“…The values ranged from 5.10 to 5.85, being close to those obtained by Azene et al (2011) and Fagundes and Yamanishi (2001) for the same type of papayaSolo (5.00-5.80 and 5.20-5.71, respectively) ( Table 6). Generally, papaya fruit pH is above five, once it has a low organic acid content (FAGUNDES;YAMANISHI, 2001).…”
Section: Phsupporting
confidence: 87%
“…Therefore, the lower rates of weight loss at 5°C in comparison to those at 10°C may be a result of lowered respiration and transpiration rates at lower temperatures [20]. Because temperature influences the respiration rate which follows the Arrhenius model, it is expected that the cumulative weight losses and average water vapour transmission rates would be larger at higher storage temperatures [21,22], and weight losses higher than 3-6% reduce considerably the quality attributes of fresh produces as reported by Parry [23].…”
Section: Weight Lossesmentioning
confidence: 99%
“…The drop in the pH values at the end of the storage period is caused by alterations in the structure of the pectins, due to the pectic enzymes, which result in fruit softening. This increase in the concentration of the organic acid produced by enzymatic hydrolysis of the pectins, could be the probable reason for the lowered pH (Azene, Workneh, & Woldetsadik, 2014). These authors propose that the tendency for the increase in the pH value observed in postharvest treatment 'green' during storage period is due to the fact that when fruit maturation continues, the organic acids decrease.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, coating the fruit with hydroalcoholic extract of the green rosemary type propolis may have slowed down the ripening process of the papaya. Azene et al (2014) found that the pH of the papaya 'Solo' ranges from 5.0 to 5.8. The fruit analyzed showed pH in the range which corresponds to the results obtained by the authors.…”
Section: Resultsmentioning
confidence: 99%